Associating farmers’ perception of climate change and variability with historical climate data in Okpuje, southeastern Nigeria - Ezeh, Jane Onyinyechi; Madukwe, Edith Uzoma; Ezeh, Christopher (Journal of Agricultural Sciences (Belgrade), 2022)
The farmers’ perception of climate change (CC) and variability in Okpuje was assessed and compared with historical climate data analysis. The farmers perceive an occurrence of change that is affecting their farm activities. However, they lack the scientific knowledge of the change that is affecting their agribusinesses. Hence some answered that they don’t know the cause of the change while others attribute it to god’s vengeance. The perception of rising temperature and delay in the onset of the rainy season are corroborated by the analysis of the climate data. The trend analysis indicates that temperature is significantly rising while rainfall has a decreasing trend. While temperature is increasing at the rate of 0.14OC per decade, the rainfall is decreasing at the rate of 8.5 mm per decade.  The onset of the rainy season is tending towards late-onset dates and early cessation. However, the perception of increasing rainfall in the area was not upheld by the trend analysis of the rainfall data. The difference might be due to high variability in rainfall in space and time. There has been increasing rainfall lately which might have posed difficulty for the human memory as closer events are remembered more easily than distant events and hence can be unravelled via a scientific approach. Nevertheless, since perception shapes adaptation, the people’s indigenous perceptions and experiences should form part of intervention measures and policies for CC adaptation to command greater participation and wider acceptance. Thus, farmers’ perceptions provide vital information but would be more reliable if integrated with scientific data analysis for policy and decision-makers in CC science, implying that none of them should be relegated but integrated.
Keywords: Climate change and variability, Rainfall, Temperature, Perception, Nigeria.